2020
DOI: 10.1111/coin.12313
|View full text |Cite
|
Sign up to set email alerts
|

Opening the black box: Personalizing type 2 diabetes patients based on their latent phenotype and temporal associated complication rules

Abstract: It is widely considered that approximately 10% of the population suffers from type 2 diabetes. Unfortunately, the impact of this disease is underestimated. Patient's mortality often occurs due to complications caused by the disease and not the disease itself. Many techniques utilized in modeling diseases are often in the form of a “black box” where the internal workings and complexities are extremely difficult to understand, both from practitioners' and patients' perspective. In this work, we address this issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Then the inferred latent variable probabilities were employed to predict a target complication earlier than the actual occurrence time (in the right-hand side). This figure also revealed that [5] The proposed methodology of this research, in other works [26], are combined with pattern mining approaches to validate the target hidden variables and enhance the understanding of the sub-types of the disease based upon the developing disease complications.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Then the inferred latent variable probabilities were employed to predict a target complication earlier than the actual occurrence time (in the right-hand side). This figure also revealed that [5] The proposed methodology of this research, in other works [26], are combined with pattern mining approaches to validate the target hidden variables and enhance the understanding of the sub-types of the disease based upon the developing disease complications.…”
Section: Discussionmentioning
confidence: 74%
“…Whilst this ratio for HYP is ({1:5}. [1] It is possible to show patterns of complications for each single visit with respect to any combination of complication co-occurrences, chosen from C as demonstrated in [26]. [2] For more information see Supplementary Material (Pre-processing and Data Structure).…”
Section: Data Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…The proposed hybrid methodology to find explainable subgroup of patients by personalising diabetic patients in precision medicine. This figure is an abstract methodology explained in Figures 1-4 in the previous work in [83].…”
Section: The Suggested Methodologymentioning
confidence: 99%
“…Among these, studies on explaining unknown risk factors and identifying temporal phenotypes by using hybrid methods (including descriptive and predictive) are rare to find in literature. It represented the reason of the earlier research conducted by the author in [32,33,[83][84][85]. The current work of this chapter's author has attempted to address these issues in the previous research in [32,33,84], after describing the case study data as a starting point, the suggested methodology is explored as a framework for modelling real time-series clinical data.…”
Section: The Suggested Methodologymentioning
confidence: 99%